2015
DOI: 10.1111/bjhp.12178
|View full text |Cite
|
Sign up to set email alerts
|

Task‐switching ability protects against the adverse effects of pain on health: A longitudinal study of older adults

Abstract: Objective Aging is often accompanied by increases in pain, which may threaten physical health. Successfully managing increased pain requires the ability to switch attention away from the pain and toward adaptive health cognitions and behaviors. However, no study to date has tested how pain interacts with task-switching ability to predict future health in older adults. Additionally, no study has tested whether objective (i.e., task-switching performance) or subjective measures of cognitive ability have a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…captured poorer performances), and had the strongest concurrence with self‐reported difficulties in our study. Several other studies have found the Trail‐making test B to be sensitive to the cognitive differences between persons with and without chronic pain (Weiner et al., ; Tesio et al., ), and to be predictive of chronic pain outcomes (Attal et al., ; Boggero et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…captured poorer performances), and had the strongest concurrence with self‐reported difficulties in our study. Several other studies have found the Trail‐making test B to be sensitive to the cognitive differences between persons with and without chronic pain (Weiner et al., ; Tesio et al., ), and to be predictive of chronic pain outcomes (Attal et al., ; Boggero et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…These components all reflect general health, and each individual component prospectively predicts morbidity and mortality (Clark et al, 1995; DeSalvo, Bloser, Reynolds, He, & Muntner, 2006; Volpato et al, 2001). The combination of measures more accurately captures a person’s overall health than any individual measure in isolation (Boggero, Eisenlohr-Moul, & Segerstrom, 2016). To create the composite ill-health variable, Z-scores were computed for each of the variables and averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Executive functions are interrelated cognitive abilities including task‐switching and working memory that allow people to plan and organize behavior. Task‐switching and working memory have been linked to adaptive pain outcomes (Berryman et al, , ; Boggero, Eisenlohr‐Moul, & Segerstrom, ; Solberg Nes et al, ). Physiologically, resting heart rate variability is a measure of parasympathetic inhibition, reflects SR ability (Segerstrom & Solberg Nes, ), and serves as a resource for managing pain (Hassett et al, ; Koenig, Jarczok, Ellis, Hillecke, & Thayer, ).…”
Section: Study 1: Individual Differences In Pain Thresholds Pain Inhmentioning
confidence: 99%